The Role of Innovation on Employees’ Satisfaction among SMEs in Ado-Odo/Ota, Local Government Area, Ota, Ogun State - Henry E. SAMUEL; Mosunmola ADEYEYE; Emmanuel O. EFE-IMAFIDON; Kayode OJO (Communications of International Proceedings, 2021)
Innovation has long been regarded as a strategic technique of enhancing an organisation's success. Studies have shown that an organization's innovative practices have a beneficial impact on employee’s work satisfaction. Lack of innovation not only hinders employees’ satisfaction but also impedes the achievements of an organization. Considering this, the study examined the role innovation played on employee satisfaction among selected SMEs within different sectors in Ado – Odo/Ota, local government area of Ota, Ogun state. The sample size for this study was 153 respondents who are business owners, managers, supervisors, or staff of selected SMEs. The analyses were done using the frequency distribution table and the multiple regression techniques on SPSS version 23. Findings from the study show that more than half of the SMEs (115, 77.2%) have only existed for less than 5 years and were mostly (52, 34.9%) within the age group 33-37 years. Further, the multiple regression analyses result revealed a significant association between innovation and employee satisfaction. The R-value = 0.85 which means that the indicators of innovation (i.e., encouragement of employees to come up with new ways of doing things, the introduction of innovative products/services, deployment of the tested way of delivering products/services, and developing ways to improve internal processes) as adopted in the study explained 85 percent of the variation in the outcome variable. The ANOVA table shows that the F-statistic was 93.3; P= 0.000. This means that the four indicators of innovation such as encouragement of employees to come up with new ways of doing things, the introduction of innovative products/services, deployment of the tested way of delivering products/services, and developing ways to improve internal processes jointly have a highly significant effect on employee satisfaction. Of the four indicators, SME's ability to encourage employees to come up with new ways of doing things (t-statistic = 11.7; p< 0.01) and being able to introduce innovative products/services (t-statistic = 6.4; p
Keywords: Employees’ happiness; satisfaction; and innovation